THE EFFECT OF OWNERSHIP STRUCTURE ON INCOME SMOOTHING - Dudi Pratomo; Kurnia Kurnia; Adli Dzil Ikram (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
Income smoothing is an earnings management action by raising or lowering earnings to make it look more stable. This was done by company management for reasons not achieving the company's targets. In financial statements, a stable company profit illustrates that the company had good business continuity.Explained in the concept of corporate governance, institutional ownership, government ownership, and managerial ownership were believed to be able to minimize the occurrence of income smoothing. Therefore, this research was conducted to determine the effect of institutional ownership, government ownership, and managerial ownership with profitability and leverage control variables on income smoothing both simultaneously and partially in BUMN companies listed on the Indonesia Stock Exchange in 2012 - 2017.The technique used to select samples was purposive sampling technique. In the process, 10 research samples were obtained with a period of 6 years, so that 60 sample units were obtained. Then, to carry out the analysis, the analytical method used logistic regression analysis with the software used SPSS 23.0.After the analysis of this study, the results stated that simultaneous institutional ownership, government ownership, and managerial ownership with profitability control variables and leverage had a significant influence on income smoothing. Furthermore, partially the results of this study stated that government ownership had a significant effect on the negative direction of income smoothing. While the other two independent variables, namely institutional ownership and managerial ownership variables did not have a significant effect on income smoothing.